2020
DOI: 10.1002/ente.202000250
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Uniform Chemical Corrosion of Metal Electrode of p–i–n Type of Perovskite Solar Cells Caused by the Diffusion of CH3NH3I

Abstract: Although perovskite solar cells have shown high power conversion efficiency, performance stability is still insufficient. Herein, the decay kinetics of the p–i–n type of perovskite cells under light illumination is monitored. It is found that the degradation of the performance is mainly caused by the decrease in short‐circuit current (JSC), which is directly related to the loss of active area. Secondary ion mass spectrometry (SIMS) analysis confirms that both CH3NH3+ and I− migrate toward the metal electrode d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
(79 reference statements)
2
14
0
Order By: Relevance
“…For example, Ma et al . found that both CH 3 NH 3 + and I − can migrate towards the Al electrode through a PC 61 BM layer, resulting in the chemical corrosion of the Al electrode and the degradation of the perovskite film [ 189 ]. In particular, CH 3 NH 3 I is highly acidic and can react with Al as shown below: …”
Section: Interfacial Chemical Reactionsmentioning
confidence: 99%
“…For example, Ma et al . found that both CH 3 NH 3 + and I − can migrate towards the Al electrode through a PC 61 BM layer, resulting in the chemical corrosion of the Al electrode and the degradation of the perovskite film [ 189 ]. In particular, CH 3 NH 3 I is highly acidic and can react with Al as shown below: …”
Section: Interfacial Chemical Reactionsmentioning
confidence: 99%
“…However, experimental findings have shown ionic migration transport to ETLs, HTLs, and contact interfaces. 10,11 For this purpose, Calado et al 12 considered ions to be stationary in ETL and HTL. Their results showed changes in the high density of mobile ions, charge collection, and screening of the electric field by ion redistribution in the absorber layer under steady-state conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The power conversion efficiency (PCE) of perovskite solar cells (PSCs) has been rapidly improving in the past decade owing to their tunable bandgap, [1][2][3] high absorption coefficient, [4][5][6] high charge mobility, 7,8 low exciton binding energy, [9][10][11] long carrier diffusion length, [12][13][14] simple process 15,16 and low manufacturing cost. [17][18][19] The PCE of normal (n-i-p) PSCs exceeds 25.5%, 20 while that of inverted PSCs has reached 23.0%.…”
Section: Introductionmentioning
confidence: 99%